Early Life Factors Associated with Adult-Onset Systemic Lupus Erythematosus in Women - Parks, Christine G.; D’Aloisio, Aimee A.; Sandler, Dale P. (Frontiers in Immunology, 2016)
Background: Exposure early in life can influence adult disease and immunity, but the role of early life exposures in risk of SLE is not established. Methods: Women in a national cohort (ages 35-74) provided data on perinatal, maternal and sociodemographic factors, longest residence to age 14 and residential farm history of at least 12 months to age 18. Cases (N=124) reported SLE diagnosed age 16 years or older with use of disease modifying anti-rheumatic drugs. Non-cases (N=50,465) did not report lupus. Odds ratios (OR) and 95% confidence intervals (CI) were estimated by logistic regression adjusting for age and race/ethnicity. Results: SLE was associated with low birthweight (data on 84 cases and 36,477 non-cases; <2500 vs. 3000-<3500 grams; OR=2.2, 95%CI 1.2, 3.9) and premature birth (57 cases and 22,784 non-cases; >4 weeks early vs. full-term; OR=3.4; 95%CI 1.6, 7.4). Considering longest childhood residence to age 14, SLE was associated with more frequent pesticide use (e.g., at least monthly OR=2.3; 95%CI 1.3, 4.1). SLE was associated with having an early and extended childhood farm residence (i.e., prenatal/maternal farm exposure and longest childhood farm residence; OR=1.8; 95%CI 1.1, 3.0 versus neither). In those with a childhood-only farm residence of 12+ months, agricultural pesticide use was associated with SLE, with the strongest associations for direct personal exposures. Conclusions: The association of SLE with premature birth is consistent with studies in other populations, and with an observed association with low birthweight. The associations of SLE with childhood exposure to residential and agricultural pesticides warrant further study. INTRODUCTION Systemic lupus erythematosus (SLE) is an autoimmune disease characterized by immune reactivity to multiple nuclear components and inflammation, resulting in diverse clinical features and multiple organ involvement. The causes of SLE are generally not known. Racial disparities and increased familial risk suggest a genetic predisposition. It is believed that environmental factors may contribute to the development of disease, but knowledge on specific risk factors is mostly limited to occupational exposures[1]. The developmental origins hypothesis has been proposed for many adult-onset, chronic inflammatory diseases, including systemic lupus erythematosus (SLE) [2-6]. Exposures during and after gestation, including nutritional, infectious, chemical